Morphology and phylogeny of Avicennia marina (Forssk.) Vierh. in Iran - Farrokh Ghahremaninejad (PLoS ONE, 2026)
Mangrove forests along the Iranian coast of the Persian Gulf are valuable both economically and for biodiversity. The main tree species in these forests is Avicennia marina (Forssk.) Vierh. The habitats of this species in Iran are separated by several thousand kilometers from other populations worldwide. Although introgressive hybridization is common in this species, no morphological study has evaluated this issue in Iranian populations. This study investigated the morphological variation of Iranian A. marina and used sequencing of ITS regions to infer phylogenetic relationships Iranian A. marina populations and other Avicennia species. Morphological analyses based on pollen grains and internodes have shown differences between A. marina populations which is the main species of the mangrove forests of Iran and a new population was identified, which is here described as A. marina subsp. australis . The phylogenetic analysis based on the ITS region confirmed the monophyly of Iranian populations and secondary analysis of ITS2 has moderate support from the two populations detected in the present study. Divergence time estimates suggest these lineages separated during the Pliocene-Pleistocene transition, likely due to climatic fluctuations and sea-level changes.